Effect of summer intermission on skeletal muscle of adolescent soccer players - Amigo, N.; Cadefau, J. A.; Ferrer, I.; Tarrados, N.; Cusso, R. (The Journal of Sports Medicine and Physical Fitness, 1998)
BACKGROUND: To study the effect of some weeks of rest on three groups of adolescent soccer players, who had undergone systematic training for eleven months. METHODS: Experimental design: Retrospective and comparative investigation; duration 4-8 weeks. Setting: young amateur players from a Spanish football club were examined at the beginning and at the end of the summer rest period. Participants: 37 young soccer players aged 14, 15 and 16 years old. They were members of three football teams. Interventions: during the rest period they were free from any training program. Measures: biopsies of M. vastus lateralis were taken immediately after training and after the summer holidays. The type, percentage and diameter of the fibers, as well as the enzymes of glycogen metabolism (glycogen synthase and glycogen phosphorylase), glycolysis (phosphofructokinase and lactate dehydrogenase), oxidative metabolism (succinate dehydrogenase and citrate synthase) and creatine kinase and transaminase (aspartate and alanine aminotransferase) were studied. RESULTS: Detraining had an adaptation effect, decreasing the cross-sectional area of type I and type II fibers, and decreasing the activities of creatine kinase, citrate synthase, phosphofructokinase, lactate dehydrogenase and aspartate aminotransferase. CONCLUSIONS: The results can help trainers to plan the length of the rest period between training.